Mathematical modeling of Elbrus glaciers in the 21st century. Part 2. Forecasting glacier evolution and lake formation under various SSP scenarios - T. Postnikova N.; O. Rybak O.; A. Gubanov S.; H. Zekollari; M. Huss; Т. Постникова Н.; О. Рыбак О.; А. Губанов C.; X. Зеколлари; М. Хусс (IGRAS, 2024)
Probable scenarios of future changes in the Elbrus glaciers and associated with them phenomena such as formation of glacial lakes and remaining ice masses buried under the debris cover are considered. The SSP scenarios (SSP1–1.9, SSP1–2.6, SSP2–4.5, SSP3–7.0, SSP5–8.5) were used for of future climate forcing. Glacier dynamics was simulated using the GloGEMflow model, which was improved by including a module of evolving debris cover. According to the prognostic calculations of the surface mass balance of the glaciers, the loss of ice mass on the Elbrus will accelerate until the end of the 2030s, reaching approximately –1.1±0.3 m w. e. yr. –1 . The volume of the glacier ice is expected to be reducing almost linearly until about 2040, after which the mass loss rate will slow down. Under the warmest climate change scenarios (SSP5–8.5, SSP3–7.0), almost all of the remaining ice masses in the North Caucasus will be concentrated on Elbrus by the end of the century. At the same time, by 2100 the glaciers of Elbrus themselves will retreat up to 4000 m above sea level and higher. In case of moderate warming (SSP1–1.9, SSP1–2.6) the position of glacier fronts maybe stabilized at an altitude of 3600–3700 m. The study concerns also the dynamics of the debris cover, predicting its doubling in area and average thickness of 0.22 m by 2040. Although the effect of the debris cover on the total volume of ice on Elbrus is estimated to be minimal, it can temporarily slow down melting of the frontal parts and areas of dead (remaining) ice. According to our estimates, the retreat of the Elbrus glaciers may result in formation of up to 17 new lakes, of which six may potentially be temporarily dammed by dead (remaining) ice zones (up to 60 m thick for Djikaugenkioz). It is expected that the largest lake may be formed on the Djikaugenkioz plateau, it will be dammed by moraine with ice buried under it in the period from 2035 to 2045 if no sufficiently efficient runoff channels will appear. The approximate time and place of formation of ...